MODEL ANALISIS DAMPAK SOSIAL EKONOMI KEBIJAKAN PEMBANGUNAN JALAN LINGKAR SELATAN DI KOTA CILEGON (Hasil Penelitian Hibah Bersaing/Terapan Kemenristek Dikti Tahun Kedua) - Ipah Ema Jumiati; Leo Agustino; Rahmawati Rahmawati (Jurnal Administrasi Publik, 2016)
Model analysis of the socioeconomic impact of South Ring Road development policy inCilegon City, on first year research obtained a description of the areas affected bysocio-economic impacts, either positive or negative effects in addition to theidentification of policy tools at the local level (local government) in overcoming theproblems of socio-economic southern ring road. This condition seemed to be a demandsupplycycle due to the lack of control on both the impact, causing both the socialimpacts to surface. Looking at the various phenomena and problems found, the authorintends to examine more deeply in the proposed second year of research on ModelAnalysis of Social Economic Impact Development Policy South Ring Road in CilegonCity in order to produce a design/model analysis of the impact of development is amodel of heightened economic and social empowerment in order to applicable andbeneficial to Cilegon city government to improve the quality of life and well-being ofpeople in Cilegon in general and the people who live around that areas in particular ina sustainable manner. Designs in this study, using a qualitative descriptive approach inthe form of case studies that focus on a particular unit of the various phenomena thataims to describe, summarize a variety of conditions, different situations or variousphenomena of social reality. The resulting model in this study is that the model of socioeconomicanalysis of the impact of development policies south ring road Cilegon needto require regulation, the readiness of the Human Resources (HR), Institutional,Financial and Technology Infrastructures.